MALE LEADERSHIP IN WOMEN’S FOOTBALL: A LONGITUDINAL ANALYSIS OF COACHING AND REFEREE POSITIONS - Passero, Julia Gravena; Barreira, Júlia; Tamashiro, Lucas; Scaglia, Alcides José; Galatti, Larissa Rafaela (Movimento, 2020)
This study analyzes female participation in coaching and referee positions in the Brazilian Women’s Football Championship since its first edition in 2013 until 2019. We analyzed the number of women coaches, assistant coaches, physical trainers, massage therapists, goalkeeper coaches, physiotherapists, and doctors. We also collected data about referees. We found male predominance ( 86%) in coaching positions with a slow increase in the number of women over the years. Female presence seemed to be higher in referee positions. We found 39% of women working as referees and 59% as assistant referees. We noted that their participation in coaching and referee positions in the Brazilian Women’s Football Championship has been slowly increasing in recent years, but gender inequality remains in leadership and visibility positions.